2002
DOI: 10.1123/jsep.24.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire sur l’Ambiance du Groupe: A French-Language Instrument for Measuring Group Cohesion

Abstract: The present report provides a summary of five studies undertaken to develop a French-language instrument to assess cohesiveness in sport teams—the “Questionnaire sur l’Ambiance du Groupe” (QAG). For the initial version of the instrument, the Group Environment Questionnaire (Carron, Widmeyer, & Brawley, 1985) was translated into French using the protocol outlined by Vallerand (1989). However, psychometric analyses undertaken in Studies 1, 2, and 3 failed to yield acceptable evidence of construct validity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 0 publications
2
28
0
2
Order By: Relevance
“…Therefore, for this test, known-group Downloaded by [Fondren Library, Rice University ] at 12:34 18 November 2014 difference validity was not supported. This is an interesting finding, as research with older populations (e.g., Brawley, Carron, & Widmeyer, 1987;Heuzé & Fontayne, 2002) found differences in perceptions of cohesion based on sport type. This serves to highlight the importance of a cohesion inventory for children.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, for this test, known-group Downloaded by [Fondren Library, Rice University ] at 12:34 18 November 2014 difference validity was not supported. This is an interesting finding, as research with older populations (e.g., Brawley, Carron, & Widmeyer, 1987;Heuzé & Fontayne, 2002) found differences in perceptions of cohesion based on sport type. This serves to highlight the importance of a cohesion inventory for children.…”
Section: Discussionmentioning
confidence: 61%
“…When Carron et al (1985) validated the GEQ, and Heuzé and Fontayne (2002) validated their French-language cohesion inventory (Questionnaire sur l'Ambiance du Groupe), they suggested that perceptions of cohesion would differ based on sport type and team tenure. Insofar as sport type was concerned, these authors predicted that cohesion would be stronger in participants from team (e.g., volleyball) versus individual (e.g., track and field) sports.…”
Section: Introductionmentioning
confidence: 99%
“…Cohesion: We also use the Tunisian version of the Questionnaire "l'Ambiance du Groupe" (QAG; Heuzé & Fontayne, 2002, the French version of the group environment questionnaire, Carron and al., 1985). This questionnaire (QAG-T) includes 18 items evaluating four dimensions of cohesion (i.e., individual attractions to the group task (ATG-T, four items); individual attractions to the group-social (ATG-S, five items); group integration-task (GI-T, five items); group integration-social (GI-S, four items).…”
Section: Measurementioning
confidence: 99%
“…Presently, researchers who desire to use the GEQ beyond the intended target population must either make a case for the appropriateness of the existing version for their specific use and/or alter items and analyses to suit as necessary. In fact, these practices have been engaged in with some degree of regularity for other activity types (e.g., exercise classes; Carron & Spink, 1993) and cultures (e.g., French sample; Heuzé & Fontayne, 2002) with varying levels of success. The age of participants (i.e., 18-30) for which the GEQ was intended has also restricted its use or forced researchers to consider alternatives to item wording as suggested by Carron, Brawley, and Widmeyer (2002).…”
mentioning
confidence: 99%